STUDENTS DREEM FROM PRE-CLINICAL TO CLINICAL YEARS - A CROSS SECTIONAL ANALYSIS FROM REHMAN MEDICAL COLLEGE, PESHAWAR. - Raza, Ali; Tanwir Khaliq (Journal of Ayub Medical College Abbottabad, 2022)
Background: Educational environment is a key indicator of student learning and reflects quality of education and curriculum. With the boom of medical colleges in the private sector, parents put great stress on education and educational environment. The purpose of this study was to investigate the difference in perceptions regarding educational environment between pre-clinical and clinical year MBBS students and to determine year wise strengths and weaknesses of the MBBS program. Methods: The study utilized the cross-sectional study design and employed, Dundee Ready Educational Environment Measure (DREEM) questionnaire. The survey included 142 pre-clinical (1st and 2nd year MBBS) and 185 clinical students (3rd to Final year MBBS). Results: The total DREEM score for the program was 119/200. Total score for pre-clinical years was 120/200 and that for clinical years was 118/200. There was no statistically significant difference between students’ perceptions of pre-clinical and clinical years. When the sub scale analysis was done, perceptions of learning (POL) (p=0.007), perceptions of teachers (POT) (p=0.003) and social self-perception (SSP) (p=0.025) scales showed statistically significant difference between pre-clinical and clinical years. Academic self-perception (ASP) and perceptions of atmosphere (POA) showed no statistically significant difference. Conclusion: About the educational environment perception students regarded it as more positive than negative. Pre-clinical students were more satisfied than clinical students except for SSP scale. Students pointed out weaknesses in the curriculum especially for teaching and learning and in the atmosphere, more so for clinical students than pre-clinical students. Findings of this study guide that emphasis shall be put on teaching development and CME activities and regular feedback mechanisms for both students and faculty members. et al. Measuring Students’ Perceptions of the Educational Climate of the New Curriculum at the Pontificia Universidad CatÏƒlica de Chile: Performance of the Spanish Translation of the Dundee Ready Education Environment Measure (DREEM). Educ Health (Abingdon) 2009;22(1):112.